PENINGKATAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN KARTU HURUF LAPAR PADA ANAK USIA 4–5 TAHUN DI TK TENERA BENGKULU UTARA - Sofianita Aritonang; Nur Hazizah; Rakimahwati; Tisna Syafnita (STKIP Subang, 2026)
This study aimed to improve the ability of children aged 4–5 years to recognize and distinguish letter forms, as well as to increase their learning interest at TK Tenera, North Bengkulu. The subjects of this study were 23 children. The learning media used was the Hungry Letter Card game, a brightly colored box-shaped medium containing uppercase and lowercase letters with a slot at the top. Through this game, children were asked to insert picture cards into the appropriate letter box based on the initial sound of each picture. The use of this medium was based on the concept of early literacy, which emphasizes that letter recognition is an important foundation for the development of children’s reading skills. Concrete, visual, and attractive media are also considered appropriate for the characteristics of early childhood learners because they can help improve children’s understanding, memory, and active participation in learning. This study employed Classroom Action Research using the Kemmis and McTaggart model, conducted in two cycles. The results showed an improvement in children’s abilities, from an average of 48% in the Developing category in Cycle I to 85% in the Very Well Developed category in Cycle II. Therefore, the Hungry Letter Card game is effective in improving children’s ability to recognize and distinguish letters, while also making the learning process more concrete, enjoyable, and meaningful for early childhood learners.